Growth effects of government expenditure in Nigeria: Does the level of corruption matter? - Iliyasu, Ibrahim; Muhammed, Ibrahim (Asian Journal of Economics and Empirical Research, 2023)
A strand of literature suggests that an efficient government can complement private capital formation and boost the overall productivity of private economic agents. Nigeria has experienced uneven growth performance in the last three decades despite growing government expenditure. This paper carried out an empirical analysis of direct and indirect links among growth, government expenditure and corruption in Nigeria using annual time series data for the period from 1990 to 2020. The autoregressive distributed lag (ARDL) model was used to explore the long-run interacting effect of corruption on the nexus between growth and government expenditure. For the robustness check, the fully modified ordinary least squares (FMOLS) and dynamic ordinary least squares (DOLS) were used as alternative techniques of estimation. Directly, an increase in government expenditure and a reduction in corruption has a significant increasing effect in the short-term and long-term growth. Indirectly, reducing corruption enhances the increasing effect of government expenditure on economic growth. However, corruption reduction up to the 42.25 threshold and beyond diminishes the increasing effect of government expenditure on economic growth. This suggests that attaining sustained growth is possible by raising government expenditure and minimizing corruption. Thus, minimizing corruption associated with expenditure policy should be a top policy priority.